A critical review on natural compounds interacting with the plant plasma membrane H+‐ATPase and their potential as biologicals in agriculture. Issue 2 (26th February 2022) - Havshøi, Nanna W.; Fuglsang, Anja T.
Abstract: The plant plasma membrane (PM) H + ‐ATPase is an essential enzyme controlling plant growth and development. It is an important factor in response to abiotic and biotic stresses and is subject to tight regulation. We are in demand for new sustainable natural growth regulators and as a key enzyme for regulation of transport into the plant cell the PM H + ‐ATPase is a potential target for these. In this review, we have evaluated the known non‐protein natural compounds with regulatory effects on the PM H + ‐ATPase, focusing on their mechanism of action and their potential as biologicals/growth regulators in plant production of future sustainable agriculture. Abstract : The plant plasma membrane H + ‐ATPase is regulated by protein kinases and by natural compounds. This review evaluates the findings and mechanisms of regulation by natural compounds. Surprisingly, many compounds affect membrane properties and not the enzyme directly.